The Effects of Number and Quality of Transferred Blastocysts on Birth Outcomes in Frozen-Thawed Transfer Cycles - Yuhu Li; Liuguang Zhang; Ping Yu; Ning Li; Bo Ma (IMR Press, 2023)
Background: There are few studies evaluating the effects of number and quality of transferred blastocysts on birth outcomes in frozen-thawed transfer cycles. Methods: A retrospective study was conducted, encompassing 5493 frozen-thawed blastocyst transfer cycles from January 2019 to June 2021. The cycles were categorized into five groups based on the number and quality of transferred blastocysts, as well as trichotomized based on maternal age brackets. Pregnancy outcomes such as implantation rate (IR), clinical pregnancy rate (CPR), multiple pregnancy rate (MPR), abortion rate (AR), live birth rate (LBR), and neonatal characteristics were compared and statistically analyzed. Results: The data revealed that maternal age, quality and number of the transferred blastocysts exerted a demonstrable impact on both pregnancy and birth outcomes. Within the same blastocyst transfer groups, it was noted that IR, CPR, and LBR exhibited a progressive decline as a function of advancing maternal age. Amplifying the number of homogeneously graded blastocysts for transfer did not conspicuously elevate CPR and LBR; however, it led to a statistically significant escalation in MPR (p < 0.01). In instances of dual blastocyst transfers, better-quality blastocysts yielded higher IR, CPR, MPR and LBR. Furthermore, neonatal outcomes were most favorable in singleton births, followed in sequence by dizygotic twins and monozygotic twins. A positive correlation was observed between sex ratio and the proportion of good-quality blastocysts, with a statistically significant difference between good-quality and poor-quality blastocyst groups (1.34 vs 1.00, p/odds ratio (OR)/95% confidence interval (95% CI) <0.01/1.33/1.10-1.62). Conclusions: Single blastocyst transfer appears to be an efficacious strategy for decreasing MPR while achieving favorable pregnancy and birth outcomes. Nonetheless, it should be noted that this strategy may engender a skewed sex ratio among the neonates.